Media release - Palmer, Mick (Michael James)
tag=1 data=Media release tag=2 data=Palmer, Mick tag=8 data=FORESTS tag=9 data=TIWI LAND COUNCIL%TIMBER PRODUCTIONTHURST ISLAND%SYLVATECH LTD%WOODCHIPS%HEADS OF AGREEMENT%FORBIO tag=24 data=PRIMARY INDUSTRY AND FISHERIES tag=27 data=K-0497-97 tag=34 data=PRSS tag=61 data=05 tag=62 data=Jun tag=63 data=1997